THU0748-HPR Evaluation of adherence to biologic disease modifying anti-rheumatic drugs in patients with inflammatory arthritis. (12th June 2018) - Lim, Y.C.; Teo, W.G.; Eng, M.N.; Cheen, H.M.; Tay, X.Y.; Yeo, S.I.; Lim, T.G.
Abstract : Background: In recent years, bDMARDs have revolutionised IA treatment in improving IA symptoms, as well as slowing down structural damage. However, efficacy observed in the controlled settings of clinical trials may not always translate to effectiveness in clinical practice. 1 2 Currently, there are no published studies assessing adherence to bDMARDs and its associated factors among IA patients in Singapore. Knowledge of the extent of poor adherence to bDMARDs and its risk factors can facilitate efficient implementation of interventions to improve adherence and IA outcomes. Objectives: The primary objective of the study was to assess adherence to bDMARDs among patients with IA in Singapore. The secondary objective was to identify factors associated with poor adherence to bDMARDs. Methods: A retrospective observational study was conducted at Singapore General Hospital, a 1600-bed academic medical centre. Electronic records of patients diagnosed with rheumatoid arthritis (RA), spondyloarthritis (SpA) or psoriatic arthritis (PsA) who had received at least six consecutive months of bDMARDs between 1 st January 2010 and 31 st December 2015 were reviewed. Adherence was calculated by proportion of days covered (PDC) using the following formula: PDC=[∑(number of doses×prescribed frequency)]/(total duration)×100%. Patients with PDC ≥0.80 were considered adherent. 3 Factors associated with adherence to bDMARDs were identified using multivariate logistic regression using the entire dataset and then by type of IA. Results: Among 115 patients included in the analyses, majority of the patients were Chinese (n=77, 67%) and females (n=61, 53%). Other pertinent demographics and clinical characteristics are detailed in table 1. The mean PDC was 0.82 (±0.18) and 69 (60%) patients were adherent (i.e. PDC ≥0.8). Multivariate logistic regression did not identify any factors significantly associated with adherence. Patients with SpA who previously received a bDMARD (OR=5.12; 95% CI 1.02–25.8; p=0.048) and who did not receive subsidy (OR=0.21; 95% CI 0.50–0.89; p=0.034) were found to be significantly associated with adherence. Conclusions: The findings of this study suggest that IA patients have suboptimal adherence to bDMARDs. Determinants of poor adherence remain elusive and further research into the social, psychological and environmental aspects is warranted. Measures to improve affordability of bDMARDs such as obtaining government subsidies and offering patient access schemes may improve adherence as seen in patients with SpA. References: [1] Harnett J, et al. J Manag Care Spec Pharm . 2016;22(3):209–18. [2] Koncz T, et al. Expert Opin. Biol. Ther. 2010;10(9):1367–1378. [3] Choudhry NK, et al. Am J Manag Care2009July;15(7):457–464. Disclosure of Interest: None declared